Comparison of quality of life between elderly and non-elderly adult residents in Okuma town, Japan, in a post-disaster setting - Hande, Varsha; Orita, Makiko; Matsunaga, Hitomi; Kashiwazaki, Yuya; Taira, Yasuyuki; Takamura, Noboru (PloS one, 2023)
With the growing elderly population who are susceptible to poor health, improvement of their quality of life is essential. In the post-disaster setting of the 2011 Fukushima Dai-ichi nuclear power plant (FDNPP) accident, affected municipalities such as Okuma town commenced their recovery processes and lifted evacuation orders in 2019. This study examines the differences in self-reported mental and physical health status, social functioning, risk perception, and intention to return between elderly (age ≥65 years) and non-elderly (age 20–64 years) residents. Questionnaires were distributed to current residents and evacuees of Okuma. Results revealed that the elderly had a 1.4 times higher odds ratio (95%CI 1.0–1.8, p = 0.034) for having anxiety regarding radiation-related health effects on future generations and a 1.3 times higher odds ratio (95%CI 1.1–1.5, p = 0.001) for wanting to know about the release of FDNPP-treated water into the environment than the younger group. Elderly residents also demonstrated a 2.2 times higher odds ratio for reporting poor physical health than younger residents. Clearing misconceptions and disseminating coherent information will reduce risk perception among this group. Further in-depth research regarding the disposal of FDNPP-treated water and its perceived risks is required. Health promotion through the encouragement of social participation, improvement of surroundings to facilitate healthy behaviors, and enhanced access to health services will improve the quality of life of elderly Okuma residents.